The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/nmd.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Relationship Between Long-term Posttraumatic Stress Disorder Symptoms and Coping in Australian Volunteer Firefighters

Abstract: This study examined the relationship between coping style and long-term posttraumatic stress symptoms in an Australian sample of volunteer firefighters 84 months following a bushfire disaster. A total of 277 firefighters completed 4 questionnaires to assess patterns of psychiatric morbidity. A 2-way repeated-measures analysis of variance was conducted to investigate the effect of time and disorder on coping. Firefighters evidencing distress were more likely to use both problem- and emotion-focused methods of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 63 publications
1
28
0
1
Order By: Relevance
“…Some volunteering roles put the volunteers in potentially traumatic circumstances that can severely impact their mental health. Doley, Bell, and Watt () found that 29% of the volunteer firefighters who were deployed during Ash Wednesday Bushfire disaster qualified for a PTSD diagnosis. These findings clearly illustrate that volunteers who have potentially traumatic tasks need access to coping support that is comparable to the support that paid professionals in similar roles have access to.…”
Section: Volunteer Withdrawalmentioning
confidence: 99%
“…Some volunteering roles put the volunteers in potentially traumatic circumstances that can severely impact their mental health. Doley, Bell, and Watt () found that 29% of the volunteer firefighters who were deployed during Ash Wednesday Bushfire disaster qualified for a PTSD diagnosis. These findings clearly illustrate that volunteers who have potentially traumatic tasks need access to coping support that is comparable to the support that paid professionals in similar roles have access to.…”
Section: Volunteer Withdrawalmentioning
confidence: 99%
“…Of the 32 articles, the majority (17/32) described fires that took place in North America. Seven articles described the outcomes of the firefighters who managed the 1983 Ash Wednesday bush fire in Southeastern Australia [19][20][21][22][23][24][25], while additional 2 articles discussed the 2010 Carmel Forest fire in Israel [26,27]. The authors assigned most (28/32) articles a low or moderate quality score.…”
Section: S11mentioning
confidence: 99%
“…The authors identified 11 articles that examined the mental health impact of wildland firefighting. Seven of these articles examined the same group, a cohort composed of volunteer firefighters who responded to the Ash Wednesday bushfire disaster in Australia [19][20][21][22][23][24][25]. All of these studies were of low quality.…”
Section: Mental Health Impactmentioning
confidence: 99%
See 2 more Smart Citations